The comprehension and production of later developing language constructions by Afrikaans-, English- and isiXhosa-speaking Grade 1 learners - Nel, Joanine Hester (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.